Proposal for a Method of Constructing Inclusive Urban Green Infrastructure - Fronczek-Wojciechowska, Magdalena; Kopacz, Karolina; Padula, Gianluca; Wiśniewski, Szymon; Wojnarowska, Anna (European Spatial Research and Policy, 2017)
Population ageing and growing awareness of the need for physical activity is one of the most important topics in Europe nowadays. But it should be noted that there is still no interdisciplinary and integrated approach to urban environment planning concerning physical activity of elderly people which would take into account special needs and possibilities of this particular group. Elderly people represent one of the groups which are threatened with social exclusion for different reasons. This article presents a proposal for a method of constructing a spatial system consisting of natural and anthropogenic elements of urban environment which can be interpreted as Inclusive Urban Green Infrastructure, enabling active and healthy ways of recreation, including the needs of elderly persons. It is based on the existing elements of the environment, but to create a well-functioning system in urban space it is necessary to introduce additional elements, both natural and man-created. The method refers to the spatial definition of areas for active recreation which meet the adopted, specific for elderly people, pro-health and functional requirements. Creation of such a system in cities would contribute to inclusion of this group into social life, thus boosting social coherence and integration across generations, and would also bring beneficial health results. Such infrastructure would also be of considerable importance for sustainable urban growth and improvement of the quality of urban space. The paper is based on source materials from the fields of science investigating health in connection with physiology of the process of ageing, influence of physical activity on this process, impact of negative features of the environment on the health of elderly people as well as urban space planning and development. The proposed methodology of constructing Inclusive Urban Green Infrastructure is presented on the example of Łódź, using data from the Geographic Information System (Topographic Objects Database) and population database for cities.